A metamorphic perspective on foreland flexure during intraplate orogeny: evidence for the involvement of weak lithosphere. (30th June 2015) - Walsh, Alec K.; Hand, Martin; Kelsey, David E.
Abstract Constraining depth–temperature conditions of syn‐orogenic burial metamorphism of syn‐orogenic sediments in a foreland basin provides an innovative way to investigate the thermomechanical state of the lithosphere. In central Australia, major intraplate deformation resulted in 10 km of syn‐orogenic sedimentation in a basin approximately 70 km wide. The deep level of burial in the foreland of the intraplate orogen requires the involvement of weak lithosphere with an elastic thickness of ≤20 km. The profound flexural response of the foreland region indicates that major intraplate deformation in central Australia was localised into a region of dramatically weakened lithosphere.